Modeling and Control of Second Life Batteries for Charging Station Applications - Zhang, Yueyan (My University, 2024)
Abstract Second Life Batteries (SLBs), retired from Electric Vehicles (EVs), present a promising solution for energy storage in the charging stations. Given the rapid growth of electric vehicle adoption, managing the energy demand at charging stations has become increasingly important. Utilizing SLBs can enhance sustainability and costefficiency by extending the lifecycle of battery systems, reducing waste and optimizing the overall energy management of charging stations. However, the integration and performance of these batteries in such applications remain underexplored, making it a critical area for research. In this study, a comprehensive approach is taken to model and control of SLB system for use in charging stations. Firstly, a detailed modelling framework is developed to accurately represent the behavior of batteries which includes parameter identification to reflect the degradation characteristics. To facilitate the integration of these batteries into charging stations, a DC/DC converter model is incorporated. This converter topology is essential for efficiently managing the voltage levels between the SLBs and the charging stations, ensuring compatibility of the system. Additionally, the control strategy is designed to effectively manage the charging and discharging cycles of these battery modules in a charging station scenario. This also includes optimizing the voltage performance ensuring both energy efficiency and battery longevity. The findings of this thesis highlight several key outcomes. From the modelling efforts, it is observed that SLBs exhibit specific changes in internal impedance, which must be taken into account for the reliable performance in charging stations. For the DC/DC converter, it plays a crucial role in performing proper voltage regulation between the batteries and charging stations and ensuring the system stability. In terms of control strategies, the designed approach succeeds in voltage scaling up, maintaining system stability and optimizing the operational life of the SLBs. These conclusions suggest that with appropriate modelling and control, SLBs can be an effective energy storage solution in charging stations, contributing to the broader goals of sustainability and foundations for the future integration work in charging stations.
Keywords: Keywords: Battery Model, Parameter Identification, DC/DC Converter, System Stability, Battery Longevity.